How to give effective feedback to your students - Brookhart, Susan M. (Alexandria, VA : ASCD, 2008)
Offers helpful strategies for giving effective and positive feedback to students, describing what kinds of feedback works best, and adjusting feedback to accommodate different levels of learning.
Includes bibliographical references (p. 114-115) and index.
Professional
Keywords: Communication in education; Feedback (Psychology); Teacher-student relationships; Communication in education; Feedback (Psychology); Teacher-student relationship